Drainage Basin Delineation and Quantitative Analysis of Panamaram Watershed of Kabani River Basin, Kerala Using Remote Sensing and GIS - V. S. JOHN; A. S. K. NAIR AND K. V. BAIJU (Journal of Geographical Society of India, 2013)
The morphometric analysis was carried out to determine the drainage characteristics of Panamaram watershed (PW) of Kabani river basin, Kerala, India with emphasis on fourth order sub-basins (FOSBs) using Geocoded imageries of IRS-IC LISS III FCCs (1997) of 1:50,000 scale, aerial photographs (1990) of 1:15,000 scale and Survey of India toposheets (1968) on 1: 50,000 scale. The main idea was to examine the stream properties based on the measurement of various stream attributes. The different drainage parameters studied and the measurements related to perimeter, area of sub-basins, basin length and number of rivers were determined by using Map Info 6.5 techniques. The drainage pattern of the PW is dendritic, a sixth order stream. There are 587, 135, 36 and 12 first, second, third and fourth order Hortonian streams, respectively in PW. The mean bifurcation ratio indicates that the drainage pattern is not much influenced by geological structures. The shape parameters reveal the elongation of the basin and sub-basins. The applicability of Horton’s Laws on Stream numbers, Stream lengths and Stream areas is tested by using the theory of regression by estimating theoretically bifurcation ratio, length ratio and area ratio. For the fourth order sub-basins of 1, 2, 4, 5 and 8 of PW, a second degree polynomial equation seems to be a better model than the Hortonian model.